Perilaku Politik Jawara Banten: Cermin Buram Civil Society - Ahmad Abrori (Refleksi: Jurnal Kajian Agama dan Filsafat, 2004)
For a long time, Indonesia has been an interesting locus of study regarding the relationship between tradition and modernity. By taking the case study of the Banten champions, this paper reveals the dominance of the Banten champions (rooted in local tradition) over modern devices such as bureaucracy, mass organizations, political parties, and business-oriented institutions. As a sociopolitical study, this research examines the role of champions in attempting to obtain and maintain their dominance in the Banten region. They spread the slogan "Defend Yourself, Defend the Nation, Defend the State" to the community. This slogan is nothing but a reflection of the knowledge, beliefs, and value systems they adhere to, which serve as a reference for their behavior in society, which is actually counterproductive to the establishment of civil society.